1993
DOI: 10.1111/j.1745-4530.1993.tb00164.x
|View full text |Cite
|
Sign up to set email alerts
|

ANALYSIS of the HELICAL SCREW RHEOMETER FOR FLUID FOOD

Abstract: The Helical Screw Rheometer (HSR) is being evaluated for rheological measurements of fluid food suspensions. the HSR consists of a helical screw enclosed in a tight fitting cylinder. With a closed system the inner screw is rotated creating a linearly increasing pressure differential along the axis of the screw, which is proportional to the viscosity of the fluid. This paper presents theoretical one‐ and two‐dimensional flow analyses for Newtonian fluids using both rectangular and cylindrical coordinates. For n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
(20 reference statements)
1
10
0
Order By: Relevance
“…In this paper, it is shown that the calculated shear rates at the screw root and the barrel surface are independent of the frame of reference. The magnitude of the shear rate at the barrel is always twice the magnitude of the shear rate at the screw root, as against that concluded by Tamura et al (1993).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…In this paper, it is shown that the calculated shear rates at the screw root and the barrel surface are independent of the frame of reference. The magnitude of the shear rate at the barrel is always twice the magnitude of the shear rate at the screw root, as against that concluded by Tamura et al (1993).…”
Section: Introductionsupporting
confidence: 59%
“…Recently, Tamura et al (1993) claimed that for an isothermal flow of a Newtonian fluid in a single-screw extruder the shear rates at the screw root and at the barrel surface depend upon the coordinate frame of reference, i.e., barrel-moving and screw-stationary or vice versa. In this paper, it is shown that the calculated shear rates at the screw root and the barrel surface are independent of the frame of reference.…”
Section: Introductionmentioning
confidence: 99%
“…Ait-Kadi et al (2002) and Roos et al (2006) apply a recent method known as the Couette analogy to various types of mixer geometries. Apart from paddle-type geometry (Castell-Perez et al 1991;Glenn and Daubert 2002), various researchers have used the helical screw impeller (Kemblowski et al 1988;Tamura et al 1989Tamura et al , 1993 and helical ribbon impeller (Eriksson et al 2002;Jahangiri 2008) for rheological measurements. Apart from paddle-type geometry (Castell-Perez et al 1991;Glenn and Daubert 2002), various researchers have used the helical screw impeller (Kemblowski et al 1988;Tamura et al 1989Tamura et al , 1993 and helical ribbon impeller (Eriksson et al 2002;Jahangiri 2008) for rheological measurements.…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…Such instruments measure either a torque, efflux time, velocity, pressure drop, and/or damping frequency. Tamura (1989) has written a review of common process viscometers, and an earlier review of commercial industrial viscometers can be found in Huskins (1982) as well as in Natkin (1974) and Dealy (1984).…”
Section: Introductionmentioning
confidence: 99%
“…Previous works (Tadmor and Gogos, 1979;Booy, 1981; Author Tamura, 1989) have developed the theoretical flow analysis for Newtonian fluids and power law fluids in the HSR (Appendix). A comparative study of the HSR measurements with those obtained from a rotational rheometer with cone and plate fixtures were performed to evaluate the accuracy and precision of the HSR.…”
Section: Introductionmentioning
confidence: 99%